Analysis of the Influence of CAR, LDR, NIM, BOPO, and NPL on Profitability in Conventional Banking Companies Listed on the IDX in 2017-2021 - Hutahuruk, Marice Br; Sudarno, Sudarno; Valencia, Erica; Angelina, Dian; Priyono, Priyono (International Conference on Business Management and Accounting, 2024)
This research aims to determine the effect of CAR, LDR, NIM, BOPO and NPL on profitability in conventional banking companies listed on the IDX in 2017-2021. This study uses secondary data. The sample technique in this study used purposive sampling. The number of samples obtained were 20 companies. The analytical method of this research uses descriptive analysis and several types of evaluation using the SmartPLS software. From this study it was found that only LDR and BOPO had a significant effect on profitability (ROA). Meanwhile, CAR, NIM and NPL have no significant effect on profitability (ROA).